Modeling of charge transport for an artificial synapse based on magnetic Josephson junctions (2018)
In this work we study the modelling of charge transport through a magnetic Josephson junction device with potential application in Neuromorphic computing as a synapse device; the artificial synapse was proposed by Schneider et al. (2018) and is compatible with SFQ (Single Flux Quantum) technology. We explore a modified standard Josephson junction circuit model (RCSJ) to consider thermal noise and study stochastic effects on the system, in addition, the results of an article by Russek et al. (2016) (where this model was used), were reproduced. On the other hand, a Tight Binding model combined with the Landauer formalism was proposed to study the charge transport through the junction following Xin-Qi Li and YiJing Yang (2001). Although this model does not describe superconducting phenomena, is a first step to construct a lattice model that could explain the behavior of the synaptic device